Mejorar el periodismo en zonas de crisis y conflicto; formación de la red de comunicación fronteriza para el desarrollo Ecuador-Colombia - Bernabé Fraguas, Javier (Revista Española de Desarrollo y Cooperación, 2023)
Regarding the information that mass media give to citizens, we are living a hectic period. Mass media give us information which can be classify as propaganda in some cases and as opinion or perception in others. Applying to the journalism origin, we should assert that there is no informative journalism without rigorous and proven information. It is time to claim these origins firmly and categorically.